Multi-Bandgap Monolithic Metal Nanowire Percolation Network Sensor Integration by Reversible Selective Laser-Induced Redox - Bang, Junhyuk; Jung, Yeongju; Kim, Hyungjun; Kim, Dongkwan; Cho, Maenghyo; Ko, Seung Hwan (Nano-Micro Letters, 2022)
Active electronics are usually composed of semiconductor and metal electrodes which are connected by multiple vacuum deposition steps and photolithography patterning. However, the presence of interface of dissimilar material between semiconductor and metal electrode makes various problems in electrical contacts and mechanical failure. The ideal electronics should not have defective interfaces of dissimilar materials. In this study, we developed a novel method to fabricate active electronic components in a monolithic seamless fashion where both metal and semiconductor can be prepared from the same monolith material without creating a semiconductor–metal interface by reversible selective laser-induced redox (rSLIR) method. Furthermore, rSLIR can control the oxidation state of transition metal (Cu) to yield semiconductors with two different bandgap states (Cu2O and CuO with bandgaps of 2.1 and 1.2 eV, respectively), which may allow multifunctional sensors with multiple bandgaps from the same materials. This novel method enables the seamless integration of single-phase Cu, Cu2O, and CuO, simultaneously while allowing reversible, selective conversion between oxidation states by simply shining laser light. Moreover, we fabricated a flexible monolithic metal–semiconductor–metal multispectral photodetector that can detect multiple wavelengths. The unique monolithic characteristics of rSLIR process can provide next-generation electronics fabrication method overcoming the limitation of conventional photolithography methods. Highlights: 1 A three single-phase Cu, Cu2O, and CuO monolithic nanowire network was successfully fabricated by reversible selective laser-induced redox (rSLIR) 2 Monolithic metal–semiconductor–metal multispectral photodetectors with Cu nanowire (CuNW) as an electrode and Cu2ONW/CuONW having different bandgaps were suggested.